Sistem Monitoring Struktur Jembatan dengan metode Real Time Operating System (RTOS) - Komang Deha Abhimana Kader; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Real Time Operating System (RTOS) is a new breakthrough for running multitasking processes on embedded systems. RTOS introduces the concept of Real Time, which means that the system does all existing tasks according to the specified time so that no task is carried out beyond the specified time limit. RTOS can be implemented in various fields that require a high degree of modularity, have limited resources and have a response time to events. One example is in the field of infrastructure monitoring which requires dentification of various types. Examples of infrastructure such as bridges. To implement RTOS in monitoring bridge structures using freeRTOS. FreeRTOS which is implemented uses three tasks in all sensor nodes where the first functions to monitor the load, deflection and strain on the last bridge, each task displays all data results to the computer using the serial monitor on the Arduino Uno. The data displayed in the form of loads, changes in the drop point in the middle of the bridge and changes in strain that occur on the bridge. The sensors used in monitoring the bridge prototype include load cell sensors for load measurement with the HX711 module, accelerometer sensors for deflection measurements and ultrasonic sensors for strain measurements with the Arduino Uno micocontroller. In the bridge prototype, the load is carried out three times with a load of 0 kg, 5 kg and 10 kg. The results of the loading obtained from the load, strain and deflection that occur. Then get the accuracy and response time of each task at the sensor node. From the test results, FreeRTOS has an average time of 1ms faster than without FreeRTOS and the accuracy of the sensor readings using FreeRTOS is closer to the desired result.